MORAL TREATMENT AND CONDITIONS OF SECLUSION IN THE MADHOUSE: THE LIMITS OF THE MEDICALIZATION PROCESS IN SANTIAGO, 1852 – 1891 - Torres Santibáñez, Luis (Revista de Historia Social y de las Mentalidades, 2015)
This article aims to analyze the process of  medicalization of madness in Santiago during  the second half of the nineteenth century. The  first part contains the alienists approaches for  moral treatment advocated by Chilean and  foreign doctors working in the madhouse.  The second part contains a description and  an analysis of the conditions under which  confinement was performed. It argues that  psychiatric science had little impact in the way  how the insane were locked in the madhouse,  being displaced by philanthropic criterion.  Thus, the medicalization of madness made talk  to discourses of modernity with traditional  discourses on the subject of how to lock up the  mentally ill.
Keywords: Mental disease medicalization; Moral treatment; Public order; Confinement practices